Factors influencing small farmers to participate in sugarcane loading stations in Thailand - Wongwai, Krisdakorn; Kamarulzaman, Nitty Hirawaty; Wong, Kelly Kai Seng; Ali, Fazlin (Global Academic Excellence, 2021)
Sugarcane loading stations were established in the sugarcane business in Thailand for more than ten years to decrease the transportation cost of the small farmers. However, the participation rate was rather low. The main objective of this study was to investigate the factors influencing sugarcane small farmers to join contract farming with sugarcane loading stations. Descriptive analysis was used to describe farmers’ demographic profiles and farms’ characteristics. Factor analysis was used to determine factors influencing farmers’ motivation to join with loading stations. Social participation was revealed as the factor the most influenced farmers’ motivation to join with loading stations, followed by economic constraints and individual goals, which these two factors have also significantly influenced the farmers’ motivation to join with loading stations. Conversely, the sign of education (positive) and age (negative) were estimated in the logistic regression analysis, which increases age level will reduce the small farmers’ motivation to participate in the sugarcane loading stations, and the higher education level will increase the small farmers’ motivation to participate in the sugarcane loading stations.